2008
DOI: 10.1080/00207450701392068
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Alzheimer's Disease and Vascular Dementia

Abstract: The levels of interleukin 1beta, interleukin 6, and interleukin 10 were elevated in the serum of patients with dementia. No statistically significant correlation was recorded in the interleukin levels among patients with Alzheimer's disease and vascular dementia. Also, no significant correlation was observed in the interleukin levels in the serum and the severity of dementia. However, a significant correlation was found between IL-6 and tumor necrosis factor-alpha (TNF-alpha) levels and age. The levels of IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 30 publications
5
53
1
Order By: Relevance
“…In accordance with our present results, several reports based on genome-wide association studies have shown upregulation of the IL-10 pathway in AD brains [16,17]. Furthermore, several previous studies have found increased CSF and blood levels of IL-10 in AD patients compared to healthy controls [9,18,19,20]. Indeed, IL-10 serum levels have been associated with the degree of cognitive decline and cortical atrophy in AD patients and as a consequence many authors have considered IL-10 as a potential marker of disease progression [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with our present results, several reports based on genome-wide association studies have shown upregulation of the IL-10 pathway in AD brains [16,17]. Furthermore, several previous studies have found increased CSF and blood levels of IL-10 in AD patients compared to healthy controls [9,18,19,20]. Indeed, IL-10 serum levels have been associated with the degree of cognitive decline and cortical atrophy in AD patients and as a consequence many authors have considered IL-10 as a potential marker of disease progression [21].…”
Section: Discussionsupporting
confidence: 82%
“…It is a prototypic proinflammatory cytokine and a key regulator of local tissue responses to injury and disease in the CNS [28]. Our results confirm previous findings documenting increased levels of IL-1β in brain lesions, CSF [28,29], and blood of AD patients [6,19,30,31,32,33,34]. IL-1β is supposed to have both beneficial and detrimental effects on the AD pathogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that level of IL-10 is elevated in the serum of patients with dementia but these levels do not discriminate between different types of dementia [133]. One of the mechanisms attributed to the role of IL-10 in reducing inflammation in AD is suppression of pro-inflammatory cytokines.…”
Section: Interleukin-4 (Il-4)mentioning
confidence: 99%
“…Many studies revealed a high level of proinflammatory cytokines in the blood of patients with AD [7][8][9]. Other authors reported a decrease [10] or no change of these indices level compared to control [11].…”
Section: Introductionmentioning
confidence: 99%